Highly rearranged gene orders and rapid evolutionary rates in the mitochondrial genomes of Apodida (Echinodermata: Holothuroidea) - Sun, Shao’e; Ni, Gang; Wang, Wansheng; Sha, Zhongli; Xiao, Ning; Xiaoqi, Zeng (Frontiers in Marine Science, 2023)
Mitochondrial genome (mitogenome) is a frequently-used tool for phylogenetic and evolutionary studies among metazoans, however, it was still poorly represented in some invertebrate groups, including holothurians. Apodida is one of the most ancient orders of Holothuroidea, with unique characteristics in lacking tube feet and the respiratory tree. Here, we sequenced six mitogenomes from the holothurian order Apodida (Synaptidae and Chiridotidae) and compared them with other available holothurian mitogenomes. The apodan mitogenomes present positive GC skews and negative AT skews, a pattern diametrically opposite to that found in the mitogenomes of other holothurians. The amino acid genetic distances of the 13 protein-coding genes (PCGs) were the highest between Apodida and other holothurians. The mitochondrial gene orders within Apodida were extensively rearranged at the species level, and also were unique from the arrangement patterns of other holothurians. Phylogenetic relationships based on two different criteria: (i) nucleotides sequences with all codon positions (PCG123) and (ii) Neutral Transitions Excluded model (NTE) confirmed the monophyly and basal position of the order Apodida with a long branch. The NTE phylogeny generated a low variation of branch length, but it did not ameliorate the long branch length of Apodida. The divergence time estimation suggested that the Apodida originated in the Middle Carboniferous, implying that they survived the extinction event that occurred in the boundary of the Permian and Triassic. The NTE dataset revealed younger age than that generated by PCG123 dataset. Apodida is accompanied by a faster evolutionary rate than other holothurians (0.0069 vs 0.0043 subs/s/my). The absence of tube feet and the respiratory tree may play an important role in the dramatic evolutionary changes of apodan mitogenomes.